1987
DOI: 10.3354/meps037065
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and 15N2 calibration of the acetylene reduction assay in coastal marine sediments

Abstract: Simultaneous assays of di-nitrogen fixation were carried out in sediments from Narragansett Bay, Rhode Island (USA) using the acetylene reduction technique and I5N2 tracer. The ratio of moles of acetylene reduced to moles of I5N recovered in ammonium and labile organic-N pools in estuarine sediments under anaerobic conditions ranged from approximately 10:l to nearly 100:l. The ratio of acetylene reduced to "N fixed was always significantly greater than the theoretical 3:l ratio. Rates of both acetylene reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…At the end of a 6 to 8 h incubation, depth profiles of acetylene reduction rates in the rhizosphere were made by taking duplicate 1 m1 sediment pore water samples with a syringe and needle through silicone-filled holes located at 2 cm intervals (1, 3, 5, ?, 9, 11, 13 cm depth) in the core wall. Twenty-four hour time course experiments confirmed that 6 to 8 h was the optimal incubation time in which a linear response could be measured accurately without the artifacts of a lag in response that can sometimes occur with too short a n incubation time (0.5 to 2 h), or of substrate depletion from too long an incubation time ( > l 2 h) (Capone 1982, Seitzinger & Garber 1987. The perfusion process took < 5 min per core and there was no visual indication of compaction of the core or channeling of the perfused pore water in the sandy sediments.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…At the end of a 6 to 8 h incubation, depth profiles of acetylene reduction rates in the rhizosphere were made by taking duplicate 1 m1 sediment pore water samples with a syringe and needle through silicone-filled holes located at 2 cm intervals (1, 3, 5, ?, 9, 11, 13 cm depth) in the core wall. Twenty-four hour time course experiments confirmed that 6 to 8 h was the optimal incubation time in which a linear response could be measured accurately without the artifacts of a lag in response that can sometimes occur with too short a n incubation time (0.5 to 2 h), or of substrate depletion from too long an incubation time ( > l 2 h) (Capone 1982, Seitzinger & Garber 1987. The perfusion process took < 5 min per core and there was no visual indication of compaction of the core or channeling of the perfused pore water in the sandy sediments.…”
Section: Methodsmentioning
confidence: 69%
“…Acetylene reduction rates were related to nitrogen fixation rates using the stoichiometric relationship of 1 m01 dinitrogen fixed for every 3 m01 acetylene reduced. Though this ratio is known to vary in marine sediments (Seitzinger & Garber 1987), we based our calculations on the callbration of acetylene reduction with 15N2 fixation made by O'Donohue et al…”
Section: Methodsmentioning
confidence: 99%
“…For example, in freshwater lakes the ratio of acetylene reduced to dinitrogen fixed can vary between 2.1:1 to 11.9:1 (Howarth et al, 1988). Ideally, future studies should cross-calibrate the acetylene reduction method with the 15 N tracer method (Seitzinger and Garber, 1987). Second, it is possible that the rates of acetylene reduction were not linear over the 24 h of incubation, although previous acetylene assay incubations using similar Arctic glacier cryoconite have been shown to be linear over this timescale (Telling , 2011).…”
Section: Active Nitrogen Fixation In the Marginal And Glacier Zonesmentioning
confidence: 99%
“…For scaling purposes, the halved sub-core samples were summed and extrapolated to area units using the aperture of the core. Rates of sediment acetylene reduction were scaled to fixed N 2 (as NH 4 + ) using a 3:1 molar conversion (Seitzinger & Garber 1987). An initial analysis to determine the potential for autotrophic sediment N 2 fixation in vegetated sediments showed no differences within a 2 × 2 design for oxic versus anoxic and light versus dark incubation (F = 1.76, p = 0.2), with all rates comparable to N 2 fixation rates in dark anoxic sediment.…”
Section: N 2 Fixationmentioning
confidence: 99%
“…Incubations lasted for 4 to 6 h, and were ended by shaking the bottle vigorously for 30 s, waiting 10 s to allow bubbles trapping gases to dissolve, and then the headspace was drawn into a pre-evacuated vacutainer using a double-ended needle for storage until it was run on the gas chromatograph. As for the sediments, rates of epiphyte acetylene reduction were scaled to fixed N 2 (as NH 4 + ) using a 3:1 molar conversion (Seitzinger & Garber 1987). The fixed N 2 was representative of the leaf area of the top 15 cm of the leaves incubated.…”
Section: N 2 Fixationmentioning
confidence: 99%